Solid solution strengthening of high-entropy alloys from first-principles study. (10th September 2022) - Zhang, H.L.; Cai, D.D.; Sun, X.; Huang, H.; Lu, S.; Wang, Y.Z.; Hu, Q.M.; Vitos, L.; Ding, X.D.
Highlights: Solid solution strengthening (SSS) effects in a series of conventional alloys and high-entropy alloys are investigated. Agreement between predicted and measured hardness is satisfactory for both alloys. Size misfit parameters and shear modulus misfit parameters are derived from first-principles calculations. The predicted host/alloy family-dependent fitting constants can be used to estimate the hardness of these SSS alloys. Abstract: Solid solution strengthening (SSS) is one kind of strengthening mechanisms and plays an important role in alloy design, in particular for single-phase alloys including high-entropy alloys (HEAs). The classical Labusch–Nabarro model and its expansions are most widely applicable to treating SSS of solid solution alloys including both conventional alloys (CAs) and HEAs. In this study, the SSS effects in a series of Fe-based CAs and HEAs are investigated by using the classical Labusch–Nabarro model and its expansions. The size misfit and shear modulus misfit parameters are derived from first-principles calculations. Based on available experimental data in combination with empirical SSS model, we propose fitting constants ( i.e., the ratio between experimental hardness and predicted SSS effect) for these two families of alloys. The predicted host/alloy family-dependent fitting constants can be used to estimate the hardness of these SSS alloys. General agreement between predicted and measured hardness values is satisfactory for both CAs and HEAs, implying that the proposed approach is reliable and successful.